Teachers’ Perception, Knowledge and Behaviour of Higher Order Thinking Skills (HOTS) - Sukma Nur Ardini (ETERNAL (English Teaching Journal), 2017)
This study aims at finding out teachers’ perception, knowledge and behaviour of HOTS in 2013 curriculum and finding out learning model mostly applied by the teachers. It is a descriptive qualitative study which involves 12 English teachers of SMAN 10, SMAN 12, SMAN 14, SMAN 15, and SMAN 8 of Semarang as the participants. Observation checklist, questionnaire and in-depth interview were used to obtain the data. The result showed that the teachers’ perception, knowledge and behaviour is very good (5%), good (85%), and enough (10%). Therefore, it is not enough to have this level of perception, knowledge and behaviour to achieve the 21st century skills. Problem based learning (70%) is the most used learning models among other (each 10%). It relates to teachers’ perception that problem based learning suits learning English language where problem comes first then the students find out the answer/solution. That is the reason why not all of learning models can be easily applied in the classroom. The urgency of conducting HOTS workshop is very high. The time allotment used in applying every learning model need to be reconsidered by the government.